PENERAPAN PEMBELAJARAN MATEMATIKA YANG MELIBATKAN KECERDASAN MAJEMUK DENGAN PENDEKATAN SAINTIFIK - Azin Taufik; Nuranita Adiastuty (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2017)
Abstract This research based on the result of preliminary observation at MTs Nurul Huda Beringin. Documentation of supervision by headmaster who has been held in the school, data showed that the learning mathematics with scientific approach applied by teachers are still not optimal. Based on documenttion of learning outcome students the data that there are 40% of students not reached the minimum competence criteria. Humans have nine types of intelegence, seven of the nine types of intelegence are: verbal/linguistic intelegence, visual/spatial, logical/mathematical, musical, bodily/kinesthetic, interpersonal and intrapersonal. This research is a classroom action research with qualitative descriptive approach implemented in class VII MTs Nurul Hudda Beringin, Cirebon, on the material relations and function. Based on the analysis we concluded that the study of mathematics involving multiple intelegences with scientific approach by the steps: 1) preliminary activities; 2) the core activities consist of observasing, ask, gather information, associates and communicate; and 3) the cover. While multiple intelegences involved in learning is verbal/linguistic intelegence, visual/spatial intelegence, logical/mathematical intelegence, musical intelegence, the intelegence of the body/kinesthetic, interpersonal and intrapersonal intelegence. In the first cycle, the average result of observation activities of students and teachers was 70% and 76% in the unfavorable and fairly category. In the second cycle, the average results of observation activities of students and teacher was 82% and 83%, both in good categories. In the first cycle, the achievment of students VIII-A is a total of 18 students or 46% students take the final value more than 75. In the second cycle, the achievment of student VIII-A is of the total of 31 students or 80% students obtain the final score more than 75. So the achievment learning was increasing 34% from the first cycle to the second cycle.